The Influence of Social Support and Self Esteem on Subjective Well-Being in Elderly of Pamona Utara Sub-District Poso Regency - Sry Pegiantri Tolewo; Yari Kurnaningsih; Adi Setiawan (PSIKODIMENSIA, 2019)
This study aims to determine the simultaneous influence of social support and self esteem on subjective well-being in the elderly in Pamona Utara sub-district, Poso regency. The sample in the study was 100 people and the sampling technique used was cluster sampling technique. Data collection was carried out using the Multidimensional Scale of Perceived Social Support (MSPSS), Self Esteem Scale (SES), Satisfaction with Life Scale (SWLS) and Positive and Negative Affect Schedule (PANAS). Data analysis technique uses multiple linear regression. From the results of data analysis obtained the value of F = 24.815 with a significance value of 0.000 (p